Parameters for unexpected (and expected) meanings: Auxiliary do in affirmative contexts. (July 2015) - Ranger, Graham
Abstract: The DO in "Subject DO Predicate" sentences is often associated with unexpected meaning, including contradictory uses in dialogue where DO functions as a sort of reassertive marker and in monologal contexts where a speaker short-circuits potential objections. Many instances of affirmative DO do not fit into this category, however. These involve quasi-exclamative use, non-polemical use in dialogue or gnomic confirmation. Often considered prototypical, contradictory DO represents only one possible configuration: other uses can be accounted for as paramétered variations of a single fundamental operation. Affirmative DO marks speaker endorsement. Values of affirmative DO — polemical, concessive, exclamative, etc. —are shown to result from the relation between various preconstructed subjective positions and the speaker's own position.